Oligoantigenic Diet for Epilepsy and Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A diet low in antigenic items was used to treat 6 3 children with epilepsy refractory to medication at the Depts of Neurology, Immunology, and Dietetics, The Hospital for Sick Children, Great Ormond Street, and the Institute of Child Health, London, England.